2014
DOI: 10.1371/journal.pone.0099170
|View full text |Cite
|
Sign up to set email alerts
|

White Feces Syndrome of Shrimp Arises from Transformation, Sloughing and Aggregation of Hepatopancreatic Microvilli into Vermiform Bodies Superficially Resembling Gregarines

Abstract: Accompanying acute hepatopancreatic necrosis disease (AHPND) in cultivated Asian shrimp has been an increasing prevalence of vermiform, gregarine-like bodies within the shrimp hepatopancreas (HP) and midgut. In high quantity they result in white fecal strings and a phenomenon called white feces syndrome (WFS). Light microscopy (LM) of squash mounts and stained smears from fresh HP tissue revealed that the vermiform bodies are almost transparent with widths and diameters proportional to the HP tubule lumens in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(42 citation statements)
references
References 12 publications
(19 reference statements)
1
37
0
2
Order By: Relevance
“…Bacteria found in the detritus from the culture system orally colonized the digestive tract, produced toxins and caused HP cellular dysfunction, destroyed the E, R, F and B cells, sloughed the tubular epithelium cells from the proximal to the distal region and produced inflammation, hemocytic infiltration and necrosis. Sriurairatana et al (2014) reported that when AHPNS appears, similar vermiform structures (aggregated transformed microvilli, ATM) are found in the HP and intestine, as observed in our study. Multiple functions are attributed to the HP: it serves as temporary food storage, produces and synthesizes protein, is involved with secretion of digestive enzymes and absorption of nutrients and is capable of metabolizing lipids and carbohydrate; there fore, any injures to this important organ could cause mortalities (Ceccaldi 1997, Lehnert & Johnson 2002, McGaw & Curtis 2013.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Bacteria found in the detritus from the culture system orally colonized the digestive tract, produced toxins and caused HP cellular dysfunction, destroyed the E, R, F and B cells, sloughed the tubular epithelium cells from the proximal to the distal region and produced inflammation, hemocytic infiltration and necrosis. Sriurairatana et al (2014) reported that when AHPNS appears, similar vermiform structures (aggregated transformed microvilli, ATM) are found in the HP and intestine, as observed in our study. Multiple functions are attributed to the HP: it serves as temporary food storage, produces and synthesizes protein, is involved with secretion of digestive enzymes and absorption of nutrients and is capable of metabolizing lipids and carbohydrate; there fore, any injures to this important organ could cause mortalities (Ceccaldi 1997, Lehnert & Johnson 2002, McGaw & Curtis 2013.…”
Section: Discussionsupporting
confidence: 90%
“…Their organs and tissues were removed, dissected and squash-mounted with sterile seawater, then examined under the light microscope (Lightner 1996, Morales-Covarrubias & Gómez-Gil 2014, Sriurairatana et al 2014). …”
Section: Histopathology Analysis: Sample Preservation and Processingmentioning
confidence: 99%
“…En los años siguientes y aún sin identificar la etiología, se propagó a países cercanos, afectando a Vietnam en el año 2010, Malasia en el 2011 y Tailandia durante el 2012 (NACA, 2012;FAO, 2013;Lightner et al, 2013;Sriurairatana et al, 2014). Recientemente, fue reportado en Filipinas (de-la- .…”
Section: Origenunclassified
“…Vibrio bacteria that are sensitive to environmental conditions will be very opportunistic if their abundance is above the threshold (Heenatigala and Fernando, 2016). So that, it will cause various multiple diseases in cultivated shrimp such as white feces syndrome, Enterocytozoon hepatopenaei (EHP) infection, and mass death caused by physiological symptoms caused by Vibrio bacterial infections (Jayasree et al, 2006;Sriurairatana et al, 2014;Mastan, 2015;and Aranguren et al, 2017).…”
Section: Organic Materials and Vibrio Bacteriamentioning
confidence: 99%